THE VERIFICATION OF A SUCCESS OF MTA USING IN TEACHING PROCESS - STEBILA, Ján; ĎURIŠ, Milan (Trends in education, 2008)
The main goal in our article is to summarily present research results that we have obtained by the research of the integration of a multimedial teaching aid (MTA) to a teaching process. It should point out the justness of using the MTA when teaching the road safety education in subject of technical education in 2.grade at a primary school.
Keywords: research; pedagogical experiment; multimedia; road safety education.